Dilema Penerapan Pajak Karbon di Indonesia: Antara Komitmen Lingkungan dan Ketahanan Ekonomi Industri - Farsya Arafy Herlucky, Jasmine; Angta Laudia, Leivasya (Journal of Accounting and Finance Management, 2024)
This research examines the dilemma of implementing carbon tax in Indonesia, specifically in balancing environmental commitments with industrial economic resilience. Using a mixed-method approach with sequential explanatory design, the study surveyed 511 respondents in the Greater Jakarta area. Results indicate that 81.41% of respondents rated the policy implementation effectiveness as moderate, while 82.2% considered implementation transparency to be at a moderate level. Regarding economic impact, 75.5% of respondents reported that the policy had a moderate intrusive level on the economy. These findings suggest a need to improve policy implementation mechanisms, particularly in monitoring aspects and information transparency. The study recommends a comprehensive strategy encompassing the development of industry incentive systems, periodic evaluations for more adaptive policy adjustments, and enhanced transparency and public engagement. In conclusion, a balanced approach is necessary to ensure carbon tax policies can achieve environmental objectives without causing excessive economic impact on the industrial sector and society.